2010
DOI: 10.1111/j.1360-0443.2009.02853.x
|View full text |Cite
|
Sign up to set email alerts
|

Internet‐based prevention for alcohol and cannabis use: final results of the Climate Schools course

Abstract: Internet-based prevention programs for school-age children can improve student's knowledge about alcohol and cannabis, and may also reduce alcohol use twelve months after completion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 169 publications
(142 citation statements)
references
References 30 publications
4
134
0
3
Order By: Relevance
“…There were no differences between the groups for binge drinking, cannabis use or cannabis intentions. Another study [25] reported the secondary effects of the Climate Schools course, using data from the original RCT of the program in 10 Sydney schools (n ¼ 764, M age ¼ 13.1 years) [33,34]. Results revealed that the Climate Schools: Alcohol and Cannabis course was effective in reducing truancy, psychological distress and moral disengagement for up to 12 months.…”
Section: Resultsmentioning
confidence: 94%
“…There were no differences between the groups for binge drinking, cannabis use or cannabis intentions. Another study [25] reported the secondary effects of the Climate Schools course, using data from the original RCT of the program in 10 Sydney schools (n ¼ 764, M age ¼ 13.1 years) [33,34]. Results revealed that the Climate Schools: Alcohol and Cannabis course was effective in reducing truancy, psychological distress and moral disengagement for up to 12 months.…”
Section: Resultsmentioning
confidence: 94%
“…Some studies show small beneficial effects [54][55][56][57], but results are not maintained and do not appear to generalise. Contrary to Fox's recommendation, these findings suggest that school-based approaches are delivering little in terms of preventing alcohol-related harm.…”
Section: Education Strategies For Minors and Their Parentsmentioning
confidence: 99%
“…Specifically, the Climate Schools: Alcohol Module was successful in increasing knowledge of harm minimization skills for alcohol use, decreasing pro alcohol attitudes, reducing average alcohol consumption, and reducing frequency of binge drinking and related harms in young people (Vogl et al 2009;Newton et al 2009b). The Climate Schools: Alcohol and Cannabis Module added further to this by successfully increasing cannabis-related knowledge, and decreasing the frequency of cannabis use in young people (Newton et al 2010(Newton et al , 2009b. Importantly, these programs have not only demonstrated success in reducing drug use, but have also been rated by teachers and students to be superior and more enjoyable than other drug prevention programs.…”
mentioning
confidence: 90%